Multifunctional Electrochemical Properties of Synthesized Non-Precious Iron Oxide Nanostructures - Ruby Phul; M. A. Majeed Khan; Meryam Sardar; Jahangeer Ahmed; Tokeer Ahmad (Crystals, 2020)
Magnetic Fe3O4 nanostructures for electrochemical water splitting and supercapacitor applications were synthesized by low temperature simple wet-chemical route. The crystal structure and morphology of as-acquired nanostructures were examined by powder X-ray diffraction and transmission electron microscopy. Magnetic measurements indicate that the as-synthesized Fe3O4 nanostructures are ferromagnetic at room temperature. The synthesized nanostructures have a high-specific surface area of 268 m2/g, which affects the electrocatalytic activity of the electrode materials. The purity of the as-synthesized nanostructures was affirmed by Raman and X-ray Photoelectron studies. The electrochemical activity of the magnetic iron oxide nanoparticles (MIONPs) for the hydrogen evolution reaction (HER) and supercapacitors were investigated in alkaline medium (0.5 M KOH) versus Ag/AgCl at room temperature. The electrocatalysts show low onset potential (~0.18 V) and Tafel slope (~440 mV/dec) for HER. Additionally, the specific capacitance of MIONPs was investigated, which is to be ~135 ± 5 F/g at 5 mV/s in 1 M KOH.